(untitled) (Journal of Namibian Studies : History Politics Culture, 2016)
With the possibility of invasion by the South African Union looming at the start of the First World War, the German colony of South West Africa lost access to reliable news transmissions. Governor Theodor Seitz issued daily news updates and denounced the spread of rumors, but German newspapers in the colony continued a pattern of publishing unconfirmed reports unchecked, including allegations of danger to white settlers from Africans and impelling greater government surveillance and suppression of Africans. The colony’s oldest newspaper faced censorship, not for spreading rumors, but rather for criticizing the governor. Ultimately, the colonial press under-mined the solidarity among the German settlers, and their faith in both the news and German colonial officials, establishing a climate of anxiety that inflamed racial tensions and the potential for interracial violence.